Comparative analysis of anthropometric characteristics and body composition among elite female futsal players in montenegro, north macedonia and croatia - Katanic, B.; Bjelica, D.; Sebic, L.; Preljevic, A.; Stankovic, M.; Brkic, S. (SportMont, 2023)
Anthropometric characteristics and body composition play an important role in achievements in most sports, however, there are still no specific recommendations on anthropometry-body composition for women in futsal. The research aimed to determine differences in anthropometric characteristics and body composition between elite female futsal players, members of the best futsal clubs in Montenegro, North Macedonia, and Croatia. The sample of respondents consisted of 30 elite female futsal players. The first sub-sample consisted of players from Montenegro (n=11, 19.18±2.44 yrs), the second sub-sample consisted of players from North Macedonia (n=10, 18.10±3.03 yrs), and the last sub-sample was consisted by players from Croatia (n=9, 20.33±5.17 yrs). Anthropometric characteristics and body composition were evaluated by a battery of 11 variables: body height (BH), body mass (BM), triceps skinfold (TS), biceps skinfold (BiS), back skinfold (BS), abdominal skinfold (AS), upper leg skinfold (UlS), lower leg skinfold (LlS), body mass index (BMI), fat percentage (FP), and muscle mass percentages (MP). Based on the ANOVA and post-hoc tests, findings showed that have differences between the groups in 4 anthropometric parameters such body height, body mass, abdominal skinfold, and muscle mass percentages. Female futsal players from Montenegro and Croatia have significantly higher results in parameters such as body height, body mass, and muscle mass percentages. While futsal players from Montenegro have significantly higher abdominal skinfold values than Croatia. The results suggest that there is some difference in anthropometry- body composition between groups of female futsal players, but for more complete conclusions an analysis should be performed on a larger sample of high-level female futsal players. However, despite that, this research made a significant contribution because it was the first to identify differences in anthropometric characteristics and body composition among elite female futsal players from different countries in this part of the world. In this way, it has opened the doors for further research into the anthropometry of female futsal players in this region.